Study Income of Tourism in Luangprabang Province - Silivanh, Sommay (Souphanouvong University Journal Multidisciplinary Research and Development, 2018)
This study focuses on Income of Tourism in Luangprabang Province from 2005 to 2015 by utilizes quantitative and qualitative method. The income mostly comes from, for instance, natural tourism, culture history, accommodation, and other businesses. The study uses mathematic model such as simple linear regression and multiple linear regression, and evaluate value of coefficient of regression by sum of square error. To do so, the study uses Matlab version 7.5.0(R2007b) and Microsoft office Excel 2007 for calculation to analyze the status of total income, tendency of income from tourism that sources that influence total income of Luangprabang Province. The result, generally, revealed that income of tourism of Luangprabang Province during 2005 to 2015 is increasing year by year, especially in 2008 the income reaches highest status and increased 20.01%, flowing by 13.93% in 2011, 13.25% in 2014, and 1.86% in 2009. The study from the tendency of the income from each source in accordance with the total income of 4 mathematics models by considering significance 0.01 this will get equation system at least one variable that can explain the changing of total income with the accurate of prediction of total income lowest 99.95% and highest 99.99%. In conclusion, the source of income of tourism that increases its income as number one is income from accommodation, following by natural tourism as number 2, historical tourism as number 3, and cultural tourism as number 4. The study can predict income of tourism of Luangprabang Province (y) in statistically significance of   0.01, with value of F0.01;4;6  9.148301 with the calculation of F equals 25785.909885 and coefficient-relation R2 equals 0.999942; So the accurate of F equals 99.99 % with the error prediction P as 0.000000